2008
DOI: 10.1149/1.2993160
|View full text |Cite
|
Sign up to set email alerts
|

Model-Based Analysis of Plasma Parameters and Active Species Kinetics in Cl[sub 2]∕X (X=Ar, He, N[sub 2]) Inductively Coupled Plasmas

Abstract: This work reports the influence of gas mixing ratio on the normalCl2∕Ar , normalCl2∕He , and normalCl2∕normalN2 plasma parameters, steady-state densities, and fluxes of active species in the planar inductively coupled plasma reactor. The investigation combined plasma diagnostics by Langmuir probes and quadrupole mass spectroscopy with a global (zero-dimensional) plasma model. It was shown that the dilution of Cl2 by any additive gas results in a noticeable change in both the electron temperature and dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…High electron impact dissociation rate for Cl 2 (k 15 = 1.12 9 10 -8 -1.23 9 10 -8 cm 3 s -1 compared with k 1 = 1.72 9 10 -9 -1.98 9 10 -9 cm 3 s -1 for 0-100% Cl 2 due to higher dissociation cross-section and lower threshold energy) not only maintains high rates of R33, R35 and R37 in the HBr-rich plasmas, but also provides the domination of Cl atoms in the Cl 2 -rich plasmas with n Cl =n Cl 2 ¼ 1:5 À 3:5 for 60-100% Cl 2 . The last result is in good agreement with earlier published works on both diagnostics and modeling of Cl 2 -based ICPs [26,28]. In addition, since in the HBr-rich plasmas the decay of Cl atoms is noticeably contributed by R33 and R35 (for example, k 33 n HBr þ k 35 n Br 2 ¼ 360 s À1 versus k 47 = 450 s -1 for 40% Cl 2 ), the sensitivity of modeling results to c Cl is rather low up to 60-70% Cl 2 in HBr/Cl 2 gas mixture.…”
Section: Plasma Parameters and Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…High electron impact dissociation rate for Cl 2 (k 15 = 1.12 9 10 -8 -1.23 9 10 -8 cm 3 s -1 compared with k 1 = 1.72 9 10 -9 -1.98 9 10 -9 cm 3 s -1 for 0-100% Cl 2 due to higher dissociation cross-section and lower threshold energy) not only maintains high rates of R33, R35 and R37 in the HBr-rich plasmas, but also provides the domination of Cl atoms in the Cl 2 -rich plasmas with n Cl =n Cl 2 ¼ 1:5 À 3:5 for 60-100% Cl 2 . The last result is in good agreement with earlier published works on both diagnostics and modeling of Cl 2 -based ICPs [26,28]. In addition, since in the HBr-rich plasmas the decay of Cl atoms is noticeably contributed by R33 and R35 (for example, k 33 n HBr þ k 35 n Br 2 ¼ 360 s À1 versus k 47 = 450 s -1 for 40% Cl 2 ), the sensitivity of modeling results to c Cl is rather low up to 60-70% Cl 2 in HBr/Cl 2 gas mixture.…”
Section: Plasma Parameters and Compositionsupporting
confidence: 92%
“…[27] (*0.075 at 350 K) for mono-Si surface in pure Br 2 gas. The value of c Cl & 0.05 was chosen according to our work [28] where it provided an acceptable agreement between measured and model-predicted Cl 2 /X (X = Ar, He, N 2 ) plasma parameters in the same ICP reactor as was used for the current study. This is quite close to c Cl values derived in Refs.…”
Section: -Dimensional (Global) Plasma Modelmentioning
confidence: 99%
“…Cl 2 was used as a primary etching gas for the PR-masked etching samples [15]. To investigate the impact of ICP and RF power on the etched sidewall profile, the chamber pressure, flow rate of Cl 2 , and etching time were kept identical.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, it was shown that such an approach works not bad even for more electronegative plasmas, for example, for the Cl 2 -bàsed ones. 21 Copyright: American Scientific Publishers zero-dimensional model with Maxwellian electron energy distribution function (EEDF) and with the experimental data on T e and n + as input parameters. 21 22 Though the real EEDFs are not exactly Maxwellian, such simplification for both the CF 4 -and CHF 3 -based low-pressure (p < 50 mTorr) ICPs provides the reasonable agreement between the results of plasma diagnostics and modeling.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%